Light metals 2023 - Broek, Stephen (The Minerals, Metals & Materials Series, 2023)
The Light Metals symposia at the TMS Annual Meeting & Exhibition present the most recent developments, discoveries, and practices in primary aluminum science and technology. The annual Light Metals volume has become the definitive reference in the field of aluminum production and related light metal technologies. The 2023 collection includes contributions from the following symposia: 60 Years of Taking Aluminum Smelting Research and Development from New Zealand to the World: An LMD Symposium in Honor of Barry J. Welch Alumina & Bauxite Aluminium Industry Emissions Measurement, Reporting & Reduction Aluminium Waste Management & Utilisation Aluminum Alloys, Characterization and Processing Aluminum Reduction Technology Cast Shop Technology Electrode Technology for Aluminum Production Scandium Extraction and Use in Aluminum Alloys.